Geochemistry in Argentina: from pioneers to the present - Rapela, Carlos Washington (2016)
Argentine geochemistry evolved during the nineteenth century hand in hand with other sciences. The Scotsman John J. Kyle was the first chemist to arrive in Argentina in 1862, contributing during his lifetime reports that expanded the geochemical knowledge of local natural resources. After visiting the USA and Europe (1868), Argentina’s President Sarmiento requested Hermann Burmeister (a prestigious biologist) to engage European scientists to foster the teaching and research of Natural Sciences (sensulato) in Argentina. The first to arrive, in August 1871 at the National Academy of Sciences and the university in Cordoba, was Max Siewert, a chemist from the German Martin Luther University. Siewert set up a state-of-the-art laboratory and analyzed, as Kyle had a few years before, a range of materials from waters and minerals to natural salts and biological materials. Some years later, Adolf Doring replaced Siewert. In the twentieth century, Gustavo Fester is the personality to highlight as a chemist/geochemist because he accomplished a vast task as teacher and researcher at the Universidad Nacional del Litoral and other institutions. During the 1950s and 1960s Argentine Geochemistry experienced slow but sustained growth, promoted by competent university professors such as Felix Gonzalez Bonorino, Jose Catoggio, Mario Teruggi and Carlos Gordillo. The first Geochemistry curriculum was initiated in 1958 at the Universidad Nacional de La Plata as a result of the bold initiative of Catoggio and Teruggi. Nowadays, Geochemistry is solidly established in Earth Sciences curricula and Argentine geochemical papers are found in all the international journals of the specialty.